AGENDA OF CULTIVARS AND THE REDUCTION OF PESTICIDE USE IN BRAZIL (CIPEEX, 2023)
The present work presents an important part of the 'State of the Art' scheduled for the preparation of a Master's Thesis being developed in the stricto sensu Graduate Program in Environmental Sciences at the Evangelical University of Goiás (UniEVANGÉLICA). The agenda highlights the importance of studying/employing cultivars for the reduction of pesticide use in Brazil. To achieve success, a deductive approach was employed, enhanced by bibliographic and documentary techniques, which allowed for the development of descriptive research.
Keywords: Brazil; Cultivars; Public Policy; Pesticides